Health‐related quality‐of‐life and treatment targets in myasthenia gravis. Issue 4 (30th August 2014) - Utsugisawa, Kimiaki; Suzuki, Shigeaki; Nagane, Yuriko; Masuda, Masayuki; Murai, Hiroyuki; Imai, Tomihiro; Tsuda, Emiko; Konno, Shingo; Nakane, Shunya; Suzuki, Yasushi; Fujihara, Kazuo; Suzuki, Norihiro
ABSTRACT Introduction: The aim of this study was to determine factors affecting health‐related quality of life (HRQOL) and to propose appropriate treatment targets for patients with myasthenia gravis (MG). Methods: We evaluated 640 consecutive patients with MG seen at 11 neurological centers. Two‐year follow‐up data were obtained for 282 patients. Correlations between detailed clinical factors and the Japanese version of the 15‐item MG‐specific QOL scale score were analyzed. Results: In a cross‐sectional analysis of 640 MG patients, multivariate regression revealed that disease severity, as evaluated by the MG Composite (P < 0.0001), total dose of oral prednisolone during the last year (P = 0.002), and Cushingoid appearance index (P = 0.0004), showed significant negative effects on HRQOL, but the quantitative MG score and current prednisolone dose did not. Conclusions: Achieving minimal manifestations (MM) status or better with prednisolone ≤5 mg/day was found to exert a major positive impact on HRQOL in both the cross‐sectional and 2‐year follow‐up patient samples and can be recommended as a treatment target. Muscle Nerve 50: 493–500, 2014